Community Structure Of Bivalve In The Seagrass Area, In The Malang Rapat Coastal Waters, Gunung Kijang District, Bintan Regency , Kepulauan Riau Province - Arga Sipahutar; Nur El Fajri; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Bivalve is commonly associated with seagrass community. To understand the community structure of bivalve in the seagrass area in the Malang Rapat coastal waters, a study has been conducted in May 2015. A purposive sampling method was applied. There were 3 stations with 3 line transects (100 m length)in each station and alongthetransects5 quadrants(1 x 1m) were placed. Results shown that there were 11 bivalvespecies present, they were Anadarasp., Circle sp.,Dosina sp., Gafrarium sp.,Macrrocallistasp., Megaitaria sp., Marcia sp.,Meretrix sp., paphiasp.,Tapes sp.,andTimoclea sp.In all study areas, the bivalvepresent mainly in the sandy gravel substrate. The valuesofdiversity index was 2.161-3.049, the Uniformity Index was 0.455-0.875 (categorized as moderate), the Dominance index was 0.130-0.249 (nodominant species). The waters quality parameters are as follows: temperature was 30.6-31.3 0C; depth was 0.23-0.33 m; current speed was 0.11-0.12 m/s; pH was 8; DO 7.6-7.9 mg/l and salinity was 30-310/00. Data on bivalve communitystructure and water quality parameters indicate that the aquatic environment in the study area is balance.Keyword :Bivalve, SeagrassEcosystem, Malang Rapat Village, Water quality